The Problem of the Givenness of Mental Reality - Petrosyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The article presents the issue of the givenness of mental reality. The author tries to show that the solutions to that problem have largely failed because there are more general, unresolved philosophical problems before this issue, and researchers approach the question from this or that philosophical position. According to the author, in particular, there is a prediction which prevents the solution to the problem: the prediction concerns to the immediacy and priority of the givenness of mind in the consciousness.
Keywords: mental reality, consciousness, phenomenon of consciousness, direct experience, pure experience